2005
DOI: 10.1159/000088888
|View full text |Cite
|
Sign up to set email alerts
|

German Vegan Study: Diet, Life-Style Factors, and Cardiovascular Risk Profile

Abstract: Background/Aim: Evaluation of cardiovascular risk profile in 154 German vegans. Methods: Cross-sectional study, Germany. Study instruments: 2 FFQ, 2 questionnaires, analyses of fasting venous blood samples. Results: The total study population had a low BMI (mean: 22.3 kg/m2), a moderate blood pressure (mean: 120/75 mm Hg), an extremely low consumption of alcohol (mean: 0.77 g/day) and 96.8% were nonsmokers. Moderate physical activity (PAL) was reported by nearly 50%, whereas 22.7% declared to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 62 publications
2
51
1
3
Order By: Relevance
“…Previously published results of studies do not provide a clear answer to the question of how, if at all, a vegan diet influences HDL particles. Some researchers have shown the lowering effects of a vegan diet on HDL-C concentration, which may impair its cardioprotective character [10,29]. We did not find a significant lowering effect of vegan diet on HDL-C concentration (Table 3).…”
Section: Discussioncontrasting
confidence: 57%
“…Previously published results of studies do not provide a clear answer to the question of how, if at all, a vegan diet influences HDL particles. Some researchers have shown the lowering effects of a vegan diet on HDL-C concentration, which may impair its cardioprotective character [10,29]. We did not find a significant lowering effect of vegan diet on HDL-C concentration (Table 3).…”
Section: Discussioncontrasting
confidence: 57%
“…In association with metabolic vitamin B12 deficiency, their carotid IMT and brachial flow-mediated dilation (FMD) were significantly worse than in patients with normal vitamin B12 levels [13,14]. Waldman et al [15] showed increased cardiovascular risk factors among German vegans and found that vitamin B12 was the only predictor of Hcy concentration. Hermann et al [16] reported similar findings.…”
Section: Resultsmentioning
confidence: 99%
“…A European study found the average BMI of vegetarians and vegans to be 23.3 and 22.4 respectively for men and 22.8 and 21.8 for women [7]. A study of German vegans found an average BMI of 22.3 [8]. A study of vegetarian children found that they too had lower BMI's than their meat-eating counterparts with an average BMI of 17.3 in ages 6 to 11 and average of 20.0 ages 12-18 [9].…”
Section: Risk Factorsmentioning
confidence: 99%